Cytoreductive Surgery Plus Platinum-Based Hyperthermic Intraperitoneal Chemotherapy in Epithelial Ovarian Cancer: A Promising Integrated Approach to Improve Locoregional Control. (23rd March 2016) - Petrillo, Marco; Anchora, Luigi Pedone; Scambia, Giovanni; Fagotti, Anna
Abstract : Epithelial ovarian cancer (EOC) remains the most lethal among gynecological malignancies. Evidence strongly suggests that administration of platinum-based hyperthermic intraperitoneal chemotherapy after cytoreductive surgery may represent an effective strategy to adequately treat both visible and microscopic disease, thus improving locoregional control.